EFIKASI DIRI TERHADAP KINERJA USAHA DENGAN KOMITMEN BERWIRAUSAHA SEBAGAI VARIABEL MEDIASI PADA UMKM - Titiek Ambarwati; Fika Fitriasari (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This study aims to see the effect of self-efficacy on entrepreneurial commitment, entrepreneurial commitment on performance, the influence of self on business performance with entrepreneurial commitment as a mediating variable in MSMEs. This research was conducted on MSMEs in Malang. The type of research used is explanatory research that aims to test theories or research that reject or reject theories or reject the results of pre-existing research. Respondents in this study were 70 MSMEs owner in Malang. The data technique used a questionnaire. Determination of the number of samples using the Slovin formula, purposive sampling was used. Data analysis used Partial Least Square (PLS) using SmartPLS 3.0 software. The results showed a significant influence between self-efficacy and entrepreneurial commitment. Entrepreneurial commitment significantly affected business performance, self-efficacy had no direct effect on business performance, and entrepreneurial commitment had a mediating role between self-influence and business performance. Self-efficacy by business owners can increase entrepreneurial commitment and business performance. Although there is no direct interaction between self-efficacy and business performance, it is hoped that increasing the commitment to entrepreneurship can also improve business performance. The results of this study are used as suggestions for business owners to increase commitment in business, considering other entrepreneurial values.